2014
DOI: 10.1089/jmf.2013.0116
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Detection in Hydroethanolic Extract of Pouteria torta (Sapotaceae) Leaves by HPLC-DAD and the Determination of Its Mutagenic Activity

Abstract: It is well known that phytotherapy has grown in popularity in recent years. Because a drug cannot be administered without ensuring its effectiveness and safety, the standardization and regulation of phytotherapeutic drugs are required by the global market and governmental authorities. This article describes a simple and reliable high-performance liquid chromatography-diode array detection analysis method for the simultaneous detection of myricetin-3-O-b-Dgalactopyranoside, myricetin-3-O-a-L-arabinopyranoside, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
11
0
3
Order By: Relevance
“…Dried tubers of Cyperus esculentus (tigernuts) were purchased from Bogobiri market, Calabar, Nigeria and authenticated in the Herbarium Unit of the Department of Botany, University of Calabar. Extraction was done following previously described method (Costa et al,2014) with slight modification. After removing bad tubers and dirt, the good ones were washed clean, air‐dried and crushed into fine powder using a blender (Kenwood 1.6 L, BL480 Prestons, Australia) for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Dried tubers of Cyperus esculentus (tigernuts) were purchased from Bogobiri market, Calabar, Nigeria and authenticated in the Herbarium Unit of the Department of Botany, University of Calabar. Extraction was done following previously described method (Costa et al,2014) with slight modification. After removing bad tubers and dirt, the good ones were washed clean, air‐dried and crushed into fine powder using a blender (Kenwood 1.6 L, BL480 Prestons, Australia) for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…activity. Although several extracts of different Pouteria species were previously chemically characterized, only the extract of P. torta was evaluated for its possible mutagenic activity, where Costa et al (2014) demonstrated mutagenicity for Salmonella thyphimurium and in rats. Thus far, there are no apparent data available regarding the assessment of P. ramiflora extract for mutagenic and antimutagenic actions in mammalian cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the flavonoids could be separated by the means of HPLC , GC and so on. Compared with all these means, CE analysis is much faster with less sample consumption that makes it very suitable for the analysis of these compounds .…”
Section: Introductionmentioning
confidence: 99%